Production of an eco-friendly concrete by including high-volume zeolitic supplementary cementitious materials and quicklime - Danutė Vaičiukynienė; Dalia Nizevičienė; Aras Kantautas; Gintautas Tamošaitis; Ignacio Villalón Fornés; Pavel Krivenko; Olha Boiko (Scientific Reports, 2024)
Abstract The production of ordinary Portland cement (OPC) is one of the main global causes of CO2 release to the atmosphere. However, its availability and unique characteristics as a binding material make it difficult to be substituted by eco-friendlier materials. However, OPC partial replacement with pozzolanic materials is one of the best solutions to this problem. Hence, in this study, various types of high-volume zeolite were employed as supplementary cementitious materials (SCM), substituting the OPC by up to 50 wt.% in the composition of the created mortars. Besides, quicklime and inorganic accelerators were included in some of the mortar mixtures to improve the hydration reaction and enhance its speed. The mechanical, durability and durability in sea water properties were investigated. Although the usage of SCM caused a decrease in the mechanical and durability properties of the specimens, the addition of 10 wt.% quicklime palliated this degradation by enhancing by 40% the 28-days compressive strength of the specimens and by significantly improving their durability (porosity, freeze–thaw resistance and carbonation resistance). Moreover, the mixtures were proved to be resistance to aggressive ionic environments, since their compressive strength even increased after 28-day immersion in seawater, due to the additional formation of hydration compounds.